Sertifikat Elektronik sebagai Jaminan Kepastian Hukum Kepemilikan Hak Atas Tanah di Desa Mojowatesrejo, Kecamatan Kemlagi, Kabupaten Mojokerto - Wyda Lusiana; Ratih Dwi Pangestu; Lucius Andik Rahmanto; Sunari Sunari; Ana Indrawati; Bintang Rahmatulloh (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The Community Service Program is one of the pillars of the Tri Dharma of Higher Education, namely education, research and community service. Universities not only carry out education for their students, but also carry out research and develop inno vation, as well as preserve and develop superior knowledge that is beneficial to society. This activity was carried out as an effort to provide information and knowledge about Legal Science regarding Electronic Certificates as a Guarantee of Legal Certainty of Rights i n Mojowatesrejo Kemlagi Village, Mojokerto. This counseling was attended by the village head and secretary, chairman and members of the Youth Organization, village PKK chairman and community members. The method of implementing service uses the lecture method which is carried out face to face.